2019
DOI: 10.21157/j.ked.hewan.v12i4.9028
|View full text |Cite
|
Sign up to set email alerts
|

THE ADDITION OF FRESH GARLIC (Allium sativum L) IN DUCK FEED REDUCES CHOLESTEROL CONTENT OF DUCK EGG

Abstract: The objective of this study to determine the effect of feeding fresh garlic to ducks on decrease the cholesterol level of duck eggs. This study composed of two treatment groups. The duck in the first group (control) was fed local feed without spplemente d with fresh garlic, while in the second group was fed with local feed and supplemented with 50 grams of fresh garlic/duck/day. Egg yolk cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides (TG) analysis were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
4
3
0
Order By: Relevance
“…According to the Duncanʼs multiple range test results, the differences between ducks that were not given garlic powder (0 g duckG 1 dayG 1 ), ducks that were given 3 and 6 g duckG 1 dayG 1 of garlic powder and ducks that were given 9 and 12 g duckG 1 dayG 1 were significant (p#0.05). This is in line with the study by Jaya et al 3…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…According to the Duncanʼs multiple range test results, the differences between ducks that were not given garlic powder (0 g duckG 1 dayG 1 ), ducks that were given 3 and 6 g duckG 1 dayG 1 of garlic powder and ducks that were given 9 and 12 g duckG 1 dayG 1 were significant (p#0.05). This is in line with the study by Jaya et al 3…”
Section: Resultssupporting
confidence: 94%
“…This means that supplementation of 3 g duckG 1 dayG 1 of garlic powder in feed is efficient. This is in line with the studies conducted by Jaya et al 3 and Jaya and Syamsuddin 4 who showed that supplementation of garlic powder can decrease duck blood cholesterol. The relationship between the dose of garlic powder in the feed and the total blood cholesterol levels in the ducks was linear, with the equation Y = 118.25 -0.925X and a coefficient of determination (R 2 ) of 0.3%, meaning that the higher the dose of garlic powder in the feed is, the lower the level of total blood cholesterol (35.17%).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These components can decrease cholesterol. Garlic contains active ingredients that are classified into essential oils, namely allium and scordinin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported that flavonoid in tomatoes flour ratio up to 8% in the diet can reduce cholesterol in laying hens [11], and diallyl disulfide in garlic can inhibit the formations of cholesterol and fatty acid which cause heart disease and protect the body from cancer. Studies have shown that giving raw garlic in laying duck feed results in low cholesterol duck eggs [10]. Dialyl trisulfide can prevent infection and inflammation on the lining of the brain or bone marrow.…”
Section: Introductionmentioning
confidence: 99%